Ficção e sociedade: espaço e personagem em "o céu de Suely" - Oliveira, Rayssa Mykelly de Medeiros (2014)
This dissertation aims perfoming an analysis and interpretation process of the movie O céu de Suely (Aïnouz, 2006), paying special attention to the categories of space and character, seen that they are the main categories in the filmic constitution process. The relation between these two main categories – character and space – is also one of the issues which guides our research (LINS, 1976), as long as the action development in the narrative occurs, mainly, because of this relation. Another issue in this dissertation is to observe the way Karim Aïnouz’s filmic work is embedded to the contexts of production and critical reception – by using notions as the style (BORDWELL, 2008), to manage the production context, and, to manage the critical reception context, some aspects from reception aesthetics (JAUSS, 1994), (JAUSS, 1979), from spectatorship theory (STAM, 2003) and from the social response system of the author José Luiz Braga (2006) – as a way to better understand the object and enrich the analytic process. During our investigation, we also tried to realize how social series aspects, issues as identity, identification and belonging (CANCLINI, 1997), (HALL, 2006) have contributed to the fictional creation of space and character